2023
DOI: 10.3390/jcm12031009
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Instrument-Assisted Soft Tissue Mobilization on Hydration Content in Lumbar Myofascial Tissues: A Quasi-Experiment

Abstract: Background: Instrument-assisted soft tissue mobilization (IASTM) is thought to alter fluid dynamics in human soft tissue. The aim of this study was to investigate the influence of IASTM on the thoracolumbar fascia (TLF) on the water content of the lumbar myofascial tissue. Methods: In total, 21 healthy volunteers were treated with IASTM. Before and after the procedure and 5 and 10 min later, lumbar bioimpedance was measured by bioimpedance analysis (BIA) and TLF stiffness was measured by indentometry. Tissue t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The key finding of this study is the documentation of increased stiffness of the upper trapezius muscle on the symptomatic side, confirmed by duro-and indentometry. This finding is relevant for future treatment methods, as increased stiffness carries a higher risk of causing hydration dysfunction [29], vasoconstriction, inflammation [30], and further stress injuries [31]. Furthermore, this knowledge can be used to better detect pathological tissue conditions, monitor the effects of therapy and training, and prevent sports injuries [20].…”
Section: Discussionmentioning
confidence: 96%
“…The key finding of this study is the documentation of increased stiffness of the upper trapezius muscle on the symptomatic side, confirmed by duro-and indentometry. This finding is relevant for future treatment methods, as increased stiffness carries a higher risk of causing hydration dysfunction [29], vasoconstriction, inflammation [30], and further stress injuries [31]. Furthermore, this knowledge can be used to better detect pathological tissue conditions, monitor the effects of therapy and training, and prevent sports injuries [20].…”
Section: Discussionmentioning
confidence: 96%
“…Cheatham et al [ 15 ] conducted an online survey of 853 members of the National Athletic Trainers' Association and the American Physical Therapy Association and found that the majority of respondents believed that IASTM improved ROM. Brandl et al [ 38 ] reported that the bioimpedance of tissues increases after IASTM, suggesting that IASTM reduces the water content of tissues. Then, the tissue may gain more water through a delayed supercompensatory effect [ 39 ], thereby increasing the flexibility of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In MFR treatment, the myofascial tissue is treated with a mechanical shearing motion (combination of compression and stretching) with low force and slow speed [ 27 ]. This is thought to result in a lasting change in the morphology of the fascia and also its hydration [ 25 , 26 , 29 , 30 ], because fascial tissue response to balanced, sustained stretching is more likely than to intermittent, uneven loads [ 31 ]. In addition, the numerous free nerve endings that act as proprioceptors, nociceptors, or nerve structures that innervate blood vessels could trigger a range of neuromuscular and neurovascular reflexes [ 5 , 32 ].…”
Section: Introductionmentioning
confidence: 99%